Comparison between paracervical and intracervical block before procedures on uterine cavity and cervical dilatation - M., Jayaraman Nambiar; Kurri, Hema Prasanna; Pai, Muralidhar V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Procedures like dilatation and curettage and manual vacuum aspirations are one of the commonest procedures conducted in the outpatient Department of Obstetrics and Gynecology. Objective of present study was to find out whether intracervical block is as effective as paracervical block in patients undergoing cervical dilatation and procedures on uterine cavity. Methods: Patients undergoing dilatation and curettage or manual vacuum aspiration were given either paracevrical block or intracervical block. The pain during cervical dilatation and curettage or manual vacuum aspiration were assessed on a 10 cm visual analogue scale. Results: Mean visual analogue score during dilatation was comparable in both groups. Mean visual analogue score were comparable during dilatation in both groups before curettage or manual vacuum aspiration. Mean visual analogue scores during manual vacuum aspiration or curettage was also comparable with both groups. One patient had a serious side effect of convulsion during paracervical block. Conclusions: Intracervical block is preferable to paracervical block during procedures like cervical dilatation and on procedures on uterine cavity as intracervical block requires less technical precision than paracervical block.